2014
DOI: 10.1177/1476127014543629
|View full text |Cite
|
Sign up to set email alerts
|

The influences of capital market munificence on new-venture alliance formation in emerging industries

Abstract: How do public capital markets influence alliance formation by new ventures? Resource dependency logic suggests that new ventures form fewer alliances when public capital markets are munificent because public investors demand less management control than do alliance partners. In contrast, according to the strategic behavior view, public capital market munificence can also motivate alliance formation because such munificence can enhance the returns that new-venture managers expect from using alliances. We seek t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
4
0
1
Order By: Relevance
“…Overall, with the belief that financial resources are a more common resource that applies to all industries, it could be concluded that network resources, indeed, contribute to the mobility of knowledge workers and to nodal changes in networks. This supports recent evidence that associates increases in the public capital market, as one form of resources, with the formation of new partnerships (Hoehn-Weiss and Barden, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Overall, with the belief that financial resources are a more common resource that applies to all industries, it could be concluded that network resources, indeed, contribute to the mobility of knowledge workers and to nodal changes in networks. This supports recent evidence that associates increases in the public capital market, as one form of resources, with the formation of new partnerships (Hoehn-Weiss and Barden, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…Our research also has implications for research that seeks to compare firm and industry effects in corporate strategies, as strategy research often does (e.g. Hoehn-Weiss and Barden, 2014; Madhok et al, 2015). Our evidence confirms that both the firm and industry effects matter, but differ in type specificity.…”
Section: Discussionmentioning
confidence: 93%
“…While the BTF initially focused on the firm's internal resources, subsequent research has also placed great emphasis on the importance of external (environmental) resources and their availability (Martinez-del-Rio et al, 2015;Park and Mezias, 2005;Staw and Szwajkowski, 1975). Indeed, the availability of critical resources both within and outside the firm has been shown to help shape the firm's risk orientation, organizational cognition, strategic choices and outcomes (Castrogiovanni, 1991;Hoehn-Weiss and Barden, 2014;Keats and Hitt, 1988;Nadkarni and Barr, 2008).…”
Section: Introductionmentioning
confidence: 99%